A Concept of Viruddha Ahara in Today’s Perspective - Potter, Bhagya Shree; Sharma, Ashok Kumar; Sharma, Kishori Lal; Meena, Rekh Raj; Nigam, Ayushi (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda is a science of healthy & peaceful life. Ahara (food) is one of the three Upasthambas (Sub-pillars of the body), which sustain the three main Sthambas (Pillars) of the body. Ahara is very much essential for the sustainment of life of all living beings. According to Ayurveda, it is dangerous to combine certain food items that are incompatible in terms of taste, potencies, time, state of health, place, condition of the doshas, digestive fire, cooking methods, processing quantities, and order of intake rules. According to Ayurvedic text , Viruddha or an incompatible diet refers to meals (diets) and medications that eject the doshas from their regular location but do not remove them from the body. This is known as Viruddha ahara , which causes channel obstruction and results in acute and chronic illnesses. We mindlessly follow the inappropriate food habits in the present age and get skin allergy disorders with unknown etiologies. Consumption of Viruddha Ahara has significantly increased in the modern period. This article discusses the various Viruddha Ahara that are consumed as part of modern living and describes their harmful consequences on health. Ayurveda